Salinity Distribution Pattern in Spermonde Waters Using Remote Sensing Data (Copernicus Marine Service) in 2022 - Dwi Rosalina; Lalu Penta Febri Suryadi; Katarrina Hesty Rombe; Ani Leilani; Irwana Irwana; Rangga Bayu Kusuma Haris (Jurnal Kelautan, 2024)
ABSTRACTSalinity is the total concentration of ions found in water. Salinity is important for the survival of organisms. Almost all marine organisms can only live in areas that have small changes in salinity. The aim of this research is to determine the distribution pattern of salinity in Spermonde waters in 2022 and to find out a comparative picture of the salinity distribution pattern on Kapoposang Island, Samatellu Lompo Island, Kuninggareng Lompo Island and Lanyukang Island in Spermonde waters in 2022. This research was conducted from August to October 2023 in Hasanuddin University Makassar, Makassar City, South Sulawesi Province. Research was conducted at the Indraja Laboratory, Faculty of Marine and Fisheries Sciences. The data used was satellite image data, namely CMEMS satellite image. The pattern of salinity distribution in Spermonde Waters with an average value of 34.04 ppt is the highest salinity in August, and for the average value of salinity distribution of 32.52 ppt is in January. The comparison pattern of salinity distribution in 2022 on Kapoposang Island, Lanyukang Island, and Samatellu Lompo Island has the same average value, namely the lowest January and the highest August, except for Koninggarang Lompo Island the highest average value is in September and the lowest is in January.Keywords: Salinity, Kapoposang Island, Lanyukang Island, Koninggareng Lompo Island, Samatellu Lompo Island